Determination of Superficial Dose Profile in Z-Line for Each Slice in CT.Scan Machines - V Changizi; MA Oghabian (Tehran University of Medical Sciences, 2004)
CT.Scan examinations cause high patient absorbed dose from x-ray ionizing radiation. Therefore it is necessary to obtain superficial dose profile in Z-line. In this research 11 thermoluminecent dosimeter (TLD), after calibration were located on Z line perpendicular to slice thickness. CT.Scan machines did X-ray exposures. The resultant dose profiles showed gussian shape apperience, which has severed dose reduction off the slice thickness. By attention to high patient absorbed dose in CT.Scan machines, it is better to referre that patients towards any other diagnostic methods with lower risk and reasonable quality.